2009
DOI: 10.1080/02652040802373012
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and evaluation of stomach-specific amoxicillin-loaded carbopol-934P mucoadhesive microspheres for anti-Helicobacter pyloritherapy

Abstract: The purpose of this research was to formulate and systemically evaluate in vitro and in vivo performances of mucoadhesive amoxicillin microspheres for the potential use in the treatment of gastric and duodenal ulcers, which were associated with Helicobacter pylori. Amoxicillin mucoadhesive microspheres containing carbopol-934P as mucoadhesive polymer and ethyl cellulose as carrier polymer were prepared by an emulsion-solvent evaporation technique. Results of preliminary trials indicate that quantity of emulsif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…Extended-release dosage forms with prolonged residence times in the stomach are highly desirable for the drugs with narrow absorption windows, stability problems in the intestinal or colonic environments, locally acting in the stomach, and poor solubility in the intestine (Streubel, Siepmann, and Bodmeier 2003). Recent approaches to increase the gastric residence time of drug delivery systems include bioadhesive devices (Alvisi et al 1996;Ponchel and Irache 1998;Patel and Chavda 2009), swelling devices that increase their size (Urquhart and Theeuwes 1984;Mamajek 1980), low density devices (Streubel et al 2003;and Raval et al 2007), floating systems (Deshpande et al 1997 andDave et al 2004), high density systems (Bechgaard and Ladefoged 1978;Davis et al 1986), magnetic systems, unfoldable and expandable systems, magnetic systems, superporous, biodegradable hydrogel systems (Singh et al 2000) and microparticulate systems (Patel and Chavda 2009). The otherwise-excellent concept of floating system suffers from a disadvantage that it is effective only when the fluid level in the stomach is sufficiently high.…”
Section: Introductionmentioning
confidence: 99%
“…Extended-release dosage forms with prolonged residence times in the stomach are highly desirable for the drugs with narrow absorption windows, stability problems in the intestinal or colonic environments, locally acting in the stomach, and poor solubility in the intestine (Streubel, Siepmann, and Bodmeier 2003). Recent approaches to increase the gastric residence time of drug delivery systems include bioadhesive devices (Alvisi et al 1996;Ponchel and Irache 1998;Patel and Chavda 2009), swelling devices that increase their size (Urquhart and Theeuwes 1984;Mamajek 1980), low density devices (Streubel et al 2003;and Raval et al 2007), floating systems (Deshpande et al 1997 andDave et al 2004), high density systems (Bechgaard and Ladefoged 1978;Davis et al 1986), magnetic systems, unfoldable and expandable systems, magnetic systems, superporous, biodegradable hydrogel systems (Singh et al 2000) and microparticulate systems (Patel and Chavda 2009). The otherwise-excellent concept of floating system suffers from a disadvantage that it is effective only when the fluid level in the stomach is sufficiently high.…”
Section: Introductionmentioning
confidence: 99%
“…The microspheres adhered to gastric mucous layer over an extended period of time and the release of drug from these microspheres was sustained for more than 12 hours. In vivo tests also showed that the microspheres exhibited better H. pylori clearance than amoxicillin administered as a dry powder (Patel and Chavda, 2008). In a similar study by Yellanki et al, amoxicillin-trihydrate microspheres were prepared using Carbopol ® 934P and ethylcellulose, the entrapment efficiency was between 78-86%.…”
Section: Application Of Mucoadhesive Microparticles To Eradication Ofmentioning
confidence: 96%
“…Examples of polymers used in development of mucoadhesive microspheres include chitosan and Carbopol ® 934P, which has been used by many researchers (Chickering et al, 1995, Chun et al, 2005a because of its good mucoadhesive and biodegradable properties (Patel and Chavda, 2008).…”
Section: Polymers Used In Microparticulate Drug Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…Approaches proposed to control the gastric residence of delivery systems in the upper gastrointestinal tract (GIT) include floating drug delivery systems (FDDS) [3][4][5], high-density [6,7], mucoadhesive [8,9], swelling and expanding [10], modified shape and other delayed gastric devices [2,11,12].…”
Section: Introductionmentioning
confidence: 99%